Biodegradation of blend films in soil and soil with chorume. I. PVC/PCL - Campos, A. [UNESP]; Martins-Franchetti, S. M. [UNESP]; Marconato, J. C. [UNESP]; Agnelli, J. A. M.; Monteiro, M. R. (Research Journal Biotechnology, 2007)
Blends of synthetic and biodegradable polymers can be important in attaining material plastic degradation in the environment. Biodegradation using soil and chorume (liquid waste from landfill) microorganisms is a promising area these days. This paper intends to study the PVC/PCL blend degradation in soil using aerobic biodegradation (Bartha respirometer). The morphology and structural changes of the blends were studied by FTIR, scanning electron microscopy, differential scanning calorimetry and contact angle measurements. Blend films prepared by the casting of dichloroethane solutions were buried in a Bartha respirometer containing soil and soil plus chorume and kept there for 120 days. During this time CO2 evolution was measured from time to time. The results showed that PCL films degrade faster than PVC/PCL and PVC films.
Keywords: biodegradation; blend; soil; chorume; respirometry